2009
DOI: 10.1016/j.burns.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

γδ T-cells: Potential regulators of the post-burn inflammatory response

Abstract: Burn injury induces an immunopathological response that can contribute to the development of a systemic inflammatory response (SIRS) and subsequent multiple organ failure. While, multiple immune cells type (T-cells, macrophages, neutrophils) are involved in this response, recent evidence suggests that a unique T-cell subset, γδ T-cells are central in the response to injury. While γδ T-cells represent only a small percentage of the total T-cell population, they display specific functional characteristics that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 110 publications
1
50
0
2
Order By: Relevance
“…γδ T cells regulate proinflammatory cytokine production by multiple immune cell subsets (24) and suppress cytotoxic T-cell activity against both tumor cells (25) and foreign antigens (26). In human burn wounds, γδ T cells hyper-activate macrophages (27), and therefore a potential role of γδ T cells in InvEE mice may be to attract macrophages (28,29). This would be consistent with the reduction in the number of monocytes in InvEE skin following reconstitution by TCRδ −/− bone marrow (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…γδ T cells regulate proinflammatory cytokine production by multiple immune cell subsets (24) and suppress cytotoxic T-cell activity against both tumor cells (25) and foreign antigens (26). In human burn wounds, γδ T cells hyper-activate macrophages (27), and therefore a potential role of γδ T cells in InvEE mice may be to attract macrophages (28,29). This would be consistent with the reduction in the number of monocytes in InvEE skin following reconstitution by TCRδ −/− bone marrow (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…30 Studies from our laboratory have established an important role of γ δ T-cells in burn-induced immunopathology influencing macrophage function, distal organ injury and wound repair. 17,18,31-33 Importantly, we observed that γδ T-cells are important in the recruitment of inflammatory cells to the injury site after burn, as γ δ T-cell deficient mice displayed a significant reduction in the cellular filtrate. 31 While in the study herein we have observed that the total number of T-cells at the burn wound site increases and are predominantly α β T-cells, concurrent findings have shown that the α β T-cell influx was dependent upon the presence of γ δ T-cells, as this T-cell infiltration of the wound site was not evident in mice deficient in γ δ T-cells.…”
Section: Discussionmentioning
confidence: 80%
“…15,16 Our studies have also clearly demonstrated that γδ T-cells, are central in the response to burn injury. 17,18 Nonetheless, the relationship of γδ T-cells to T-cell cytokine responses at the injury site after burn remains unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…NO has exhibited a role in fibroblast proliferation, collagen synthesis 33 and contraction of collagen lattices. 34 Also macrophage angiogenic activity (important for wound healing) is dependent on NO synthase, 34 and NO synthase activity is upregulated in tendinopathy. 35 However, one can doubt whether sufficient absorption of NO through the skin and into the degenerative area of the tendon occurs.…”
Section: Discussionmentioning
confidence: 99%